AN OPERATIONAL DATA ASSIMILATION SCHEME FOR THE MARTIAN ATMOSPHERE - Lewis, S; Read, P (1995)
A meteorological data assimilation scheme has been developed for Mars, based on techniques used for the current operational scheme at the UK Meteorological Office (UKMO). The scheme has been designed to interface with a range of models of varying complexity, from a simple primitive equations model to a full martian general circulation model with detailed parameterizations of the most important physical processes. The scheme was originally intended to be used primarily for analysis of temperature profiles from the Pressure Modulator Infrared Radiometer (PMIRR) onboard the Mars Observer (MO) spacecraft. It is, however, capable of analysing any asynoptic, randomly-distributed dataset, which may include surface pressure, temperature, velocity or constituent data originating either from other past or future spacecraft missions or from models. It is proposed to use the scheme not only for interpretation of forthcoming data from future spacecraft but also for model inter-comparisons, for hind-casting earlier martian data for model validation and for data impact studies in the planning of new missions. Initial results have demonstrated successful assimilations of trial orbiter and lander data into models with different initial conditions and physics, although a large number of landers might be required if orbiter data were not available. An optimum approach would combine orbiter data with simultaneous measurements from a small number of landers.